Pemanfaatan artificial intelligence dalam pendidikan: Peluang, tantangan dan implikasi etis - Khoiriyah, Lailatul (Maliki Interdisciplinary Journal, 2026)
The development of Artificial Intelligence (AI) has brought significant changes in various aspects of life, including in the field of education. The use of AI in education presents great opportunities to improve the quality of learning through personalized materials, efficient evaluation processes, and expanded access to digital technology-based learning. AI enables adaptive learning systems tailored to the needs, abilities, and characteristics of students, thereby supporting more effective and student-centered learning. However, behind these opportunities, the use of AI also presents a number of challenges, such as human resource readiness, low digital literacy, over-reliance on technology, and technological access gaps in various educational institutions. In addition, the use of AI in education raises ethical implications that need serious attention, particularly regarding the privacy and security of student data, potential algorithmic bias, and the shifting role of educators in the learning process. This article aims to examine the use of Artificial Intelligence in education by highlighting the opportunities, challenges, and ethical implications that accompany it. The method used is conceptual thinking through conceptual analysis and theoretical studies from various relevant literature. The results of the study show that the use of AI in education must be done wisely.